2020
DOI: 10.1007/s00423-020-01869-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications of surgery for gastro-entero-pancreatic neuroendocrine neoplasias

Abstract: Purpose Surgery is recommended for most patients with gastro-entero-pancreatic neuroendocrine neoplasias (GEP-NENs). Rates of complications and perioperative mortality have been reported in few mostly retrospective single-center series, but there has been no detailed analysis on risk factors for perioperative complications and mortality to date. Methods Data of patients with GEP-NENs operated between January 2015 and September 2018 were retrieved from EUROCRINE©, a European online endocrine surgical quality re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…In pancreatic neuroendocrine neoplasms (pNEN), the association between the surgical access [1,2], the extent of resection [3][4][5], simultaneous lymphadenectomy [6] and the patient's oncological outcome is a subject of discussion. However, severe postoperative complications are frequent and occur in 15.6% of the patients after surgery for gastroentero-pancreatic neuroendocrine neoplasm (NEN) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic neuroendocrine neoplasms (pNEN), the association between the surgical access [1,2], the extent of resection [3][4][5], simultaneous lymphadenectomy [6] and the patient's oncological outcome is a subject of discussion. However, severe postoperative complications are frequent and occur in 15.6% of the patients after surgery for gastroentero-pancreatic neuroendocrine neoplasm (NEN) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Albers et al 13 recently analysed data concerning postoperative complications using the EUROCRINE registry, a European online endocrine surgical quality registry. They included 133 patients across 23 centres from nine different countries who underwent resection of a SB‐NEN.…”
Section: Discussionmentioning
confidence: 99%
“…Because mesenteric tumour masses can have a close relationship with the main mesenteric trunks, vascularisation of the small bowel may be at risk during central mesenteric dissection. Other potential complications after surgery for SB‐NEN include postoperative haemorrhage, surgical site infections, abscess and anastomotic leakage 13 …”
Section: Introductionmentioning
confidence: 99%
“…Patients who undergo CRH for aNETs are younger and have fewer comorbidities than typical patients with colon cancer. Nevertheless, the rate of major complications after a colectomy for aNETs ranges from 5% to 15%[ 28 , 36 , 37 ]. A systematic review and meta-analysis conducted by Ricci et al [ 30 ] found that when performing a CRH in aNETs > 2 cm, the number needed to treat was five, while the number needed to harm was six, suggesting that the risk was similar to the possible benefit.…”
Section: Outcomes After a Completion Right Hemicolectomymentioning
confidence: 99%